Do deliberate firesetters hold fire-related scripts and expertise? A quantitative investigation using fire service personnel as comparisons - Butler, Helen (Psychology, crime & law, 2021)
Purpose: This research investigated, for the first time, the presence of fire-related scripts and expertise in males who have set deliberate fires.Method: One hundred and twenty-seven participants (34 firesetters, 34 offender comparisons, 34 fire service personnel, and 25 community comparisons) were asked to solve problem scenarios (e.g. destroying evidence) using fire. These scenarios were designed to tap into fire-related scripts and expertise. Other known fire-related variables (e.g. serious fire interest) were also examined using the Four Fire Factor Scales (Ó Ciardha, C., Tyler, N., & Gannon, T. A. (2016). A Practical guide to assessing adult firesetters’ fire specific Treatment Needs using the four Factor fire Scales. Psychiatry: Interpersonal and Biological Processes, 78(4), 293-304).Results: Firesetters held more scripts and were more expert in firesetting relative to Offender and Community Comparisons. However, firesetters’ responses could not be differentiated from Fire Service Personnel. A multiple regression showed that identification with fire was an important predictor of firesetting scripts, and both identification with fire and serious fire interest uniquely predicted firesetting expertise.Conclusions: This study has empirically demonstrated for the first time that firesetters hold fire supportive scripts and expertise in fire misuse. Furthermore, the inclusion of Fire Service Personnel demonstrated that both those who misuse fire and those who interact with it pro-socially exhibit cognitive and behavioural characteristics associated with the presence of fire-related scripts and expertise.